Piptocarpha longipedunculata (Asteraceae, Vernonieae) a new species of Serra do Mar, São Paulo, Brazil - Volet, Danilo Poso; Nakajima, Jimi Naoki; Monge, Marcelo; Semir, João (Phytotaxa, 2017)
Piptocarpha longipedunculata is a new species that is endemic to the São Paulo state in Brazil and occurs in the northern region of Serra do Mar. It is classified as endangered (EN) due to its limited geographic distribution. The species grows in areas of Ombrophilous Dense Forest, riparian forests and forest edges of Atlantic Forest Domain. It resembles Piptocarpha axillaris and Piptocarpha macropoda in its overall appearance, but differs mainly by its long pedunculated capitula with few flowers. Its characteristics and relationships within the genus are discussed here. Illustrations and a distribution map are also provided.